GERAKAN DAN GAGASAN ISLAM NUSANTARA DI INDONESIA - Muhammad Zein Damanik; Dimas Nugroho; Rudi Herdi Nurmawan; Manda Alief Mawadda (Jurnal At-Tabayyun, 2023)
This article examines changes and developments in the concept of Islamic thought in the archipelago, especially in Indonesia. This study examines Islamic thought throughout Indonesian culture and history. This journal examines the role of intellectuals, literature and religious institutions that have shaped Islamic identity in Indonesia from the beginning of the spread of Islam to the present. In addition, this research emphasizes interactions and conversations between Islam and local culture, which reflects the plurality and tolerance that characterize the Islamic paradigm in the archipelago. This journal provides in-depth insight into the unique contribution and complexity of Islamic thought in constructing intellectual identity in Indonesia by investigating the history of Islamic thought in Indonesia. This article will also explain how liberal Islamic ideas developed in Indonesia, the main points of liberal Islamic thought, and also in this article will explain the challenges of Islam in the current era of globalization in the archipelago.